Management Control for Microfinance: An Examination of the Belief System of a Malaysian Microfinance Provider - Siti-Nabiha A. K.; Zubir Azhar; Mohd-Aatif Ali-Mokhtar (Asian Academy of Management Journal of Accounting and Finance, 2018)
This paper examines how the belief system of a bank that provides microfinance services influences formal and informal control mechanisms and consequently shapes decisions and the strategic direction of microfinancing in Malaysia. Using institutional logics perspective as our theoretical lens, we conducted a case study in a Malaysian developmental financial institution (DFI) responsible for providing microfinancing. The results suggest that it is difficult to achieve a balance between economic and social considerations when the banking belief system is strongly rooted in the overall banking practices. This paper highlights the dominance of the banking logic over the social logic as reflected in the DFI’s management control system. Specifically, it demonstrates how its belief system underpins its microfinance activities due to a focus on risk-return considerations, which aim to minimise non-performing loans and maximise commercial profits. This consequently affects clients who have obtained microfinance products and services. This paper also demonstrates how the hiring carriers of social logic do not appear to infuse the organisation with social logic, due to the vague and compartmentalised structure of the microfinance segment and a lack of long-term social goals in both external and internal monitoring systems.